Analysis of Fresh Fruit Bunch Price Fluctuations of Oil Palm and Their Impact on Farmers' Welfare in Mukomuko Regency - Ana Nurmalia (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to analyze fluctuations in the price of oil palm Fresh Fruit Bunches in Mukomuko District and the factors that influence them. Data were collected through direct interviews and field observations and supported by secondary data from eight oil palm companies in the region. Single Exponential Smoothing and linear regression methods were used to predict price trends and analyze internal factors such as fertilizer use, crop age, marketing channels, and farmer experience. The results showed that TBS prices fluctuated significantly from 2018 to 2022, with a sharp increase in 2021-2022, influenced by government policies and international market conditions. The factors of marketing channels and age of oil palm plants were shown to have a significant influence on TBS prices. In conclusion, although the predictions show a steady upward trend in prices until 2028, price fluctuations remain a major challenge affecting smallholders' welfare. Therefore, risk management strategies are needed to protect farmers' income from the negative impact of price fluctuations.